Perempuan dan Batik : Perkembangan Peran Perempuan Dalam Industri Batik Incung di Kerinci - Nandia Pitri; Febriady Huta Uruk (LP4MK STKIP PGRI Lubuklinggau, 2023)
Kerinci is one of the regions in Jambi Province that is aggressively developing the batik industry. The batik industry that is currently developing is the Incung batik industry. Incung batik is a typical Kerinci batik with incung writing motif. The development of the batik industry that takes place in people's lives is not a work of art, but an industrial product that becomes a commodity. The development of the batik industry requires precision, accuracy, subtlety and beauty that is very suitable for the characteristics of a woman. With that, the role of women is very large in the development of the incung batik industry. The purpose of this article is to describe and analyze the important role of women in the batik industry, not only as batik craftsmen, batik entrepreneurs and housewives. In this research, history research methods are used to understand social phenomena that occur in the community directly at the research location. Hopefully this article can help increase the knowledge of women incung batik artisans in Kerinci.